SISTEM INFORMASI PENJUALAN KERAJINAN BAMBU PADA UD. TAMAN LESTARI BERBASIS WEBSITE - I Kadek Putra Agung Darmawan; Ni Wayan Sumartini Saraswati; I Dewa Made Krishna Muku (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2022)
UD. Taman Lestari is a business engaged in the sale of various kinds of bamboo and various types of handicrafts from bamboo such as processed Balinese handicrafts (klakat, sanggah solar, kulkul and others) and bamboo decoration crafts (bamboo wall lamps, water showers, tables). , and bamboo chairs). Based on the results of observations, the business process of selling bamboo at UD. Taman Lestari happened that in one day there were 5-15 customers who made purchases of bamboo and bamboo crafts which in one day customers could purchase 20 types of goods and the owner recorded purchases of goods made by customers who still used notebooks. Based on the problems above, the authors found an idea to design and build a website-based sales system, so that customers can see products that are sold online and admins can manage data and reports easily. The research method in designing this system uses the waterfall method. The final result of this research is the construction of a website as an intermediary medium for owners and customers and this research produces 2 reports, namely, transaction reports and inventory reports. The system development has passed blackbox testing.